2021
DOI: 10.5152/anatoljcardiol.2021.63668
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and central sleep apnea in the era of implantable recorders

Abstract: Sleep-disordered breathing (SDB) is a complex syndrome with a high prevalence and a significant impact on the general well-being of the overall population. Heart failure (HF) is a major health issue with an increasing incidence, a high rate of hospitalizations, and high mortality in developing countries. Focusing on early recognition and management of HF comorbidities may have an important role in reducing the economic burden and public health impact of HF. The close interconnection between HF, heart rhythm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Several prior studies have shown that the severity of HF is closely related to the prevalence and severity of SDB and CSA, and the occurrence and severity of CSA also reflect potential cardiac dysfunction. 2 , 7 , 11 CSA is often associated with elevated BNP, low LVEF, and high NYHA class, 12 , 13 , 14 and CSA prevalence increases as NYHA class deteriorates. 6 The high severity of ischemic HF may be caused by myocardial cell necrosis after long‐term ischemia, hypoxia, or myocardial infarction, which leads to a severe decline in myocardial systolic function and severe water and sodium retention, resulting in a high prevalence of SDB and CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have shown that the severity of HF is closely related to the prevalence and severity of SDB and CSA, and the occurrence and severity of CSA also reflect potential cardiac dysfunction. 2 , 7 , 11 CSA is often associated with elevated BNP, low LVEF, and high NYHA class, 12 , 13 , 14 and CSA prevalence increases as NYHA class deteriorates. 6 The high severity of ischemic HF may be caused by myocardial cell necrosis after long‐term ischemia, hypoxia, or myocardial infarction, which leads to a severe decline in myocardial systolic function and severe water and sodium retention, resulting in a high prevalence of SDB and CSA.…”
Section: Discussionmentioning
confidence: 99%